An investigation into the mediation effect of coping style on the relationship between psychological resilience and perceived stress among athletes with sports injury - Mohammadi, F. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
This study was aimed at evaluating the effect of coping styles on the relationship between psychological resilience and perceived stress among injured athletes. The statistical population included 800 players of sports teams of the Iranian national sports leagues, among whom 300 athletes were chosen as the study sample based on Morgan’s table by a purposive convenience sampling method. The study instruments were 3 standard questionnaires. Pearson Coefficient test and linear regression were used to test the hypotheses. The results showed that the dimensions of stress coping style had a significant effect on perceived stress and psychological resilience. Despite the mental and physical problems stress brings about for individuals, it seems they are not inactive toward stress. To cope with stress and its unfavorable consequences, individuals often adopt some behaviors which originate from their coping styles. As personality characteristics, approach and avoidance coping styles can help injured patients have psychological resilience.